How are Experiential Avoidance and Cognitive Fusion Associated with Alexithymia? - YILDIZ, MESUT (SPRINGER, 2021)
A transdiagnostic approach to psychiatric disorders presents an opportunity to evaluate the relationship between alexithymia and the concepts of psychopathology according to the psychological flexibility model. This study aimed to investigate the relationship between alexithymia, cognitive fusion and experiential avoidance. A total of 133 outpatient participants were included in this cross-sectional study. Sociodemographic Data Form, Toronto Alexithymia Scale-20, Acceptance and Action Questionnaire-II, Cognitive Fusion Questionnaire, Hospital Anxiety and Depression Scale, and Ten-Item Personality Inventory were used. The non-alexithymic group consisted of 37 participants while the alexithymic group of 26. The alexithymic group had higher scores in terms of depression, anxiety, experiential avoidance, and cognitive fusion. Difficulty in identifying and differentiating feelings and total alexithymia scores had positive correlations with anxiety, experiential avoidance, and cognitive fusion. In hierarchical regression analysis, the only difficulty in identifying feelings was predicted by both experiential avoidance and cognitive fusion. These results revealed that alexithymia might also be conceptualized adopting the psychological flexibility point of view.
Keywords: Alexithymia; Cognitive fusion; Experiential avoidance; Psychological flexibility; ACTION QUESTIONNAIRE-II; PSYCHOLOGICAL INFLEXIBILITY; EMOTION REGULATION; TURKISH VERSION; RELIABILITY; VALIDITY; SCALE; VALIDATION; ACCEPTANCE